Does Empowering Women and Achieving Gender Equality Contribute to Nation’s Output ? Evidence from Sub-Saharan Africa - Osundina, Olawumi Abeni (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
The relationship between women empowerment and economic growth has been a popular debate among development economists. One of the popular arguments is that women contribute more to the development of a nation where there is provision for adequate opportunities for them to develop their potentials. The aim of the study is to investigate the relationship between the dimensions of women empowerment (social, economic and political) and economic well-being in some selected 24 countries in Sub Saharan Africa (SSA) for 2001-2015 period. The empowerment variables employed are female labour force participation (economic), secondary school enrollment of females and maternal mortality rate (social), proportion of seats held by women in the national parliament (political) and gross domestic product per capita (economic well being). Results from our analysis shows that the relationship between social empowerment and economic well-being is positive while economic empowerment and economic well-being is negative. Further investigation by sub-regions of SSA reveals that there exist differences by sub-regions as there is mixed results with differences in signs. However, investigation of the relationship with the use of interaction variables between each of the social empowerment variables and economic empowerment variable reveals that labour force participation of educated female and adequate health care resources accessible by women participating in the labour force both have positive relationship with economic well-being of SSA countries. The relationship between female health, representation of women in parliament and economic well-being show positive and statistical significance. Our findings imply that in as much as it is important to provide females with adequate and equal access to education and health care resources, it is also important to provide females with equal access to productive resources, formal employments and decision making mechanisms. This is a call to policy makers and administrators to take pragmatic steps to mitigate against all forms of gender-based discrimination; remove barriers that prevents female from showcasing their potentials; empower women socially, economically and politically simultaneously. Policy makers should take note of the differences among and within countries and sub-regions in sub-Saharan Africa in the planning process. Government should also amend the constitutions to capture the needs of women.

ÖZ: Kadınların güçlenmesi ve ekonomik büyüme arasındaki ilişki, kalkınma ekonomistleri arasında popüler bir tartışma olmuştur. Popüler argümanlardan biri, kadınların, potansiyellerini geliştirmeleri için yeterli fırsatların sağlandığı bir ulusun gelişimine daha fazla katkıda bulunduklarıdır. Bu çalışmanın amacı, kadınların güçlendirilmesinin boyutları arasındaki ilişkiyi araştırmaktır (sosyal, ekonomik ve politik) ve ekonomik refah Sahra Altı Afrika’da seçilen 24 ülkede 2001-2015 dönemi için. Kullanılan güçlendirme değişkenleri kadın işgücüne katılım (ekonomik), kadınlarda ortaokul kaydı ve maternal mortalite oranı (sosyal), kadınların ulusal parlamentoda düzenledikleri koltukların oranı (siyasi) ve kişi başına gayri safi yurtiçi hasıla (ekonomik refah). Analiz sonuçlarımız sosyal güçlenme ile ekonomik refah arasındaki ilişkinin pozitif olduğunu göstermektedir ekonomik güçlendirme ve ekonomik refah olumsuz. Sahra Altı Afrika'nın alt bölgeleri tarafından yapılan daha ayrıntılı araştırmalar, işaretlerdeki farklılıklarla karışık sonuçların olduğu alt bölgelere göre farklılıklar olduğunu ortaya koyuyor. Ancak, sosyal değişkenlerden biri arasındaki etkileşim değişkeninin kullanımı ile ilişkinin araştırılması ekonomik güçlendirme değişkenleri, eğitimli kadınların işgücüne katılımının Sahraaltı Afrika ülkelerinin ekonomik refahı ile pozitif bir ilişki içinde olduğunu ortaya koymaktadır. Kadın sağlığı ile kadınların parlamentodaki temsilleri ve ekonomik refah arasındaki ilişki olumlu ve istatistiksel olarak önemlidir. Bulgularımız kadınlara eğitim ve sağlık hizmetlerine yeterli ve eşit erişimin sağlanmasının önemli olduğunu göstermektedir, kadınlara üretken kaynaklara, resmi işlere ve karar alma mekanizmalarına eşit erişimin sağlanması da önemlidir. Bu politika yapıcılar ve yöneticiler için bir çağrı her türlü cinsiyete dayalı ayrımcılığa karşı hafifletmek için pratik adımlar atmak; kadınların potansiyellerini sergilemelerini önleyen engelleri kaldırmak; kadınları sosyal, ekonomik ve politik olarak aynı anda yetkilendirmek. Politika yapıcılar, planlama sürecinde Sahra altı Afrika'daki ülkeler ve alt bölgeler arasındaki ve içindeki farklılıkları dikkate almalıdırlar. Hükümet, kadınların ihtiyaçlarını yakalamak için anayasaları da değiştirmeli.
Doctor of Philosophy in Economics. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2019. Co-Supervisor: Prof. Dr. Cem Esref Payaslıoğlu and Supervisor: Prof. Dr. Fatma Güven Lisaniler.
Keywords: Economics Department; Women in economic development--Women; Empowerment--Africa; Women in economics; Businesswomen--Women Entrepreneurship--Africa; Women empowerment; Economic well-being; Economic development; Labor force participation; Sub-Saharan Africa; GMM